IDENTIFY THE PATTERN OF URBAN GROWTH IN BANDUNG CITY USING GEOSPATIAL ANALYSIS - Sam, Dwiputra (Bulletin of Geology, 2024)
Land-use changes essentially are a side-effect of the growth of a city, which is commonly caused by urban developments. The spreading of urban developments on undeveloped land near a city (Urban Sprawl) may lead to a lackof urban planning, a lack of proper laws that regulate urban planning, and many other issues. To mitigate urban sprawl, the current study aims to determine the pattern of Bandung City's growth. The study focuses on the urban developments, that may have caused urban sprawl. The usage of time-series spatial data in an urban development analysis is typically used as the backbone of the study. Therefore, a 30 year dataset (1988-2018) is used to determine the pattern. The mean spatial method has been used to evaluate the dataset in Bandung City and the districts around the city. The method resulted in a pattern of movement resulting into the southwestern part of the city. Two points are also used to act as a pivot to determine the direction of the city's growth.The geometrical center of the study area and Gedung Sate were chosen as the pivot points. The direction of Bandung City’s growth based on the two pivot points resulted inthe Southwest direction.